2020
DOI: 10.3389/fneur.2020.598531
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Myelin Oligodendrocyte Glycoprotein Antibody-Associated Relapse With COVID-19

Abstract: A 39-year-old lady with relapsing myelin oligodendrocyte glycoprotein antibody (MOG-IgG) associated disease developed coryzal symptoms, malaise, sweating, and postural dizziness. Six days later she presented with painful progressive right visual loss consistent with optic neuritis. COVID-19 was confirmed by nasopharyngeal swab and MOG-IgG serological reversion was noted. Visual function improved following steroids and plasma exchange. This case highlights a possible causal association between inflammation due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 9 publications
(9 reference statements)
4
42
0
Order By: Relevance
“…In our patient, and the three others reported with optic neuritis, [6][7][8] COVID-19 infection presumably triggered an autoimmune response and the production of MOG antibodies. It is unclear whether the patients already had a predisposition to MOG associated disease, as in the described relapse of MOG-AD in a patient during COVID-19, 29 or if the virus set a novel process in motion.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, and the three others reported with optic neuritis, [6][7][8] COVID-19 infection presumably triggered an autoimmune response and the production of MOG antibodies. It is unclear whether the patients already had a predisposition to MOG associated disease, as in the described relapse of MOG-AD in a patient during COVID-19, 29 or if the virus set a novel process in motion.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this observation does not hold true for children where relapses can be seen irrespective of serostatus. MOG‐IgG serological reversion also remains a possibility as recently noted in a MOGAD relapse with COVID‐19 90 . On longitudinal MOG‐IgG testing, 1 study found that MOG‐IgG seroreversion occurred in 3% of cases 14 .…”
Section: Maintenance Therapiesmentioning
confidence: 83%
“…Whether negative seroversion should be defined as MOG‐IgG that is persistently undetectable or below an accepted cutoff remains unclear. The clinical relevance of this distinction was highlighted in a recent report of a MOGAD relapse with SARS‐CoV‐2 infection associated with MOG‐IgG serological reversion despite prior persistently subthreshold MOG‐IgG levels 90 …”
Section: Discussionmentioning
confidence: 99%
“…The MOG receptor is associated with MOG antibody disease (MOGAD) a neuro-inflammatory condition that may cause inflammation of the optic nerve, the spinal cord and brain. Recent research has shown that SARS-CoV2 does trigger a relapse of MOGAD (Woodhall, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the detected interactions have already been experimentally confirmed in recent literature, others provide novel insights into the pathology of SARS-CoV2. Notably, the interaction with DPP4 has been suggested to cause a higher mortality rate of diabetics contracting SARS-CoV2 (Valencia, 2020) while the MOG receptor is associated with the MOG antibody disease which relapses in SARS-CoV2 patients (Woodhall, 2020).…”
Section: Introductionmentioning
confidence: 99%